Main aspects of balanced approach in islamic rationalism - Muslihabadi, Faiza Muslihi (Journal of Oriental Studies, 2016)
The main aspects of balanced approach in Islamic rationalism have been analyzed in this paper. This method comprises material,ethical, social and spiritual aspects and contains somebody principles:* not to pass the measure and limit; * observation of the equilibrium; * unity of rational and ethical aspects.